Analisis Minat dan motivasi Belajar, Pemahaman Konsep dan Kreativitas Siswa terhadap hasil Belajar Siswa dalam Materi Geometri Selama Pembelajaran Dalam Jaringan kelas X SMA Kota Medan - Susi Sihombing (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2021)
This research is an ex-post facto research which is correlative in nature. The problems investigated in this study are the relationship between interest and creativity variables, conceptual understanding, motivation to mathematics learning outcomes. Data collected were processed using statistical analysis